SOFT SKILLS FORMATION THROUGH THE PRISM OF UNIVERSITY STUDENTS’ VIEW: ANALYSIS OF SURVEY RESULTS - Lokhvytska, Liubov; Martovytska, Nataliia; Kolomiiets, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Fundamental changes in the educational paradigm of the Ukrainian education modern system have led to a revision of the process of improving the university students’ professional training. The issue of students’ soft skills formation as mandatory for the diversification of career opportunities in the labor market is relevant. Unification with European standards has led to the necessity to fill the new content of university education to ensure personal development and self-development of future professionals in the course of mastering fundamental and special disciplines and the soft skills formation, which determines the novelty of the issue. The purpose of the study was to carry out a theoretical analysis of the problem of students’ soft skills formation and empirical study of the students’ attitude (pedagogical specialty) of Ukrainian universities to this process in the context of preparation for their future career. The main method was a survey conducted by respondents filling out an author’s questionnaire “What is an ideal preschool teacher?” in electronic form on the online platform Google. Students of the specialty 012 “Preschool Education” of the first (bachelor’s) level of higher education (1‒4 years of study) from 2 Ukrainian universities (n = 191) were included into the sample. The results were processed both quantitatively and qualitatively and demonstrated that students are aware of the need to form soft skills in preparation for their own professional activities. However, more emphasis was placed on them by senior respondents, who, having mastered a large number of specialized subjects and had various types of educational practices, realized the importance of developing skills (soft skills) for personal growth. In this regard, changes are needed in the educational and professional curriculum of the first (bachelor’s) level of higher education, where it is important to outline the task of students’ soft skills formation as a mandatory component of future professionals’ training to meet the requirements of today’s labor market.